Evaluasi Laporan Hasil Kegiatan P3 (Penerapan Perangkat Pembelajaran) Mahasiswa Pendidikan Bahasa dan Sastra - Nugroho, Agung; Hadiwinarto, Hadiwinarto; Sari, Inda Puspita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the report on the results of the P3 (Implementation of Learning Devices) activities for Study Program students. Pend. Indonesian Language and Literature STKIP PGRI Lubuklinggau. This research is focused on evaluating the P3 report (Implementation of Learning Devices) covering the systematics of reports and the use of Indonesian. This program evaluation study uses the CIPP model (context, input, process, and product). Data was collected through analysis of the results of P3 activity reports (Implementation of Learning Devices) with qualitative descriptive methods. The data were analyzed to determine the feasibility of the report from the systematic and linguistic elements. The results showed that the report on the results of P3 activities (Implementation of Learning Tools) was quite good, in terms of the systematic and linguistic elements of the report. In conclusion, the report on the results of the P3 (Application of Learning Devices) activities for STKIP PGRI Lubuklinggau students is quite good. In the future, the P3 activity report (Implementation of Learning Devices) needs to be improved again. Keywords: Report Evaluation, Implementation of Learning Tools (P3), Language and Literature